"Whenever big changes come, big talks don't": an examination of the police experience of recruitment and promotion positive action processes - Stubbs, Gareth (International journal of law, crime and justice, 2023)
Policing in England Wales is currently experiencing a large uplift in police recruitment. This has been due to the Government's target to uplift officers by 20,000. As a result, police forces are implementing large scale, sustained recruitment drives. These are accompanied by positive action schemes to address deficits in officer representation. Current statistics now indicate that representation in forces is rising slowly, as these initiatives are employed. There is little literature that examines the impact of positive action on existing police officers' perceptions, despite the initiative's relative proliferation. Procedural Justice theoretical literature is utilised to situate this in the research context. This study represents 17 theoretically informed, long form, phenomenological interviews conducted with serving officers in a uniform, response policing environment. The interviews were semi-structured, open ended and participant led, allowing the officers to present and explore their own thoughts and feelings about positive action, developed through their lived experience in an active police role. These interviews were conducted in an operational environment, from an insider-outsider perspective with total privacy. Officers openly discussed how they felt about the implementation of such policies and procedures. The findings indicate that a taboo exists with regards to the discussion of positive action processes in the police workplace. A juxtaposition also exists between the existence of positive action initiatives and the theme of meritocracy amongst the police officers. Officers strongly refuted the need for positive action to remedy issues with representation, but similarly criticised the current representation levels within forces. Theoretically this indicates an informational gap between police implementation of positive action interventions, and the perceived need for them to exist at all amongst rank and file. Implications for the study's findings are explored and possible remedies discussed.